Aptamer-enriched scaffolds for tissue regeneration: a systematic review of the literature - Parisi, Ludovica; Ghezzi, Benedetta; Toffoli, Andrea; Macaluso, Guido M.; Lumetti, Simone (Frontiers in Bioengineering and Biotechnology, 2023)
Aptamers are a brand-new class of receptors that can be exploited to improve the bioactivity of tissue engineering grafts. The aim of this work was to revise the current literature on in vitro and in vivo studies in order to i) identify current strategies adopted to improve scaffold bioactivity by aptamers; ii) assess effects of aptamer functionalization on cell behavior and iii) on tissue regeneration. Using a systematic search approach original research articles published up to April 30, 2022, were considered and screened. In total, 131 records were identified and 18 were included in the final analysis. Included studies showed that aptamers can improve the bioactivity of biomaterials by specific adsorption of adhesive molecules or growth factors from the surrounding environment, or by capturing specific cell types. All the studies showed that aptamers ameliorate scaffold colonization by cells without modifying the physicochemical characteristics of the bare scaffold. Additionally, aptamers seem to promote the early stages of tissue healing and to promote anatomical and functional regeneration. Although a metanalysis could not be performed due to the limited number of studies, we believe these findings provide solid evidence supporting the use of aptamers as a suitable modification to improve the bioactivity of tissue engineering constructs.